PERANAN LEMBAGA ADAT DALAM PROSES ENKULTURASI NILAI-NILAI KEARIFAN LOKAL TIDORE DAN PENGARUHNYA TERHADAP PEMBENTUKAN KARAKTER REMAJA DI KELURAHAN SOASIO, KOTA TIDORE KEPULAUAN - Oktosiyanti MT. Abdullah (Universitas Khairun, 2015)
The method of this researh is qualitative decriptif in exploratively design. the aim of this research is to describe the pnomena in naturally to find out the meaning and to analyze the data comprehencively, deeply naturally. The object of this research is the adat organizaton in Soasio village Kota Tidore Kepulauan and the village’ sociaty about 12-21 years. The variable is the custom organization role in character naming in five local culture. they are Mae se Kolofino (shy and afrai feeling, to the God), Ngaku se Rasai (holding belive), Budi se bahasa/oli se nyemo-nyemo (politely in talking), Suba se Tabea (politely behaviour), Cing se cingeri (merakyat dan rendah hati) and the youngers character from the sixth main character are religius, honesty, dicipline, tolerance and socially.The result of the reseach showed that the local wisdom value as the same as the main value of nation still use and anderstand well by the Soasio society. But, the value is just used and understood by the old generation and the youngers do not use and understand. In addition, it is coused the process of encilturation the Tidore local wisdom value to the Soasio youngers still lack. Key words: Enkulturasi, local wisdom value, custom organization, youngrs, character of education